An introduction to plasma physics and its space applications. - Conde, Luis (Ph. D. in physics) (IOP ebooks. 2020 collection., 2020)
This book is a brief introduction to plasma physics. The book is divided into two parts, focusing initially on molecular collisions, before moving on to examine the physical description of plasmas as a system of interacting particles. Basic concepts are introduced in a simple way and mathematical developments and demonstrations are covered thoroughly. The fundamental processes in a plasma at the atomic and molecular level are discussed, with updated experimental data sets provided. Each chapter concludes with references and commentaries for further insight in the essential points. Two important applications of plasma physics in aerospace technology are introduced in the last chapters: the electric propulsion in space and low-pressure microwave electric discharges, currently denominated multipactor and corona. The book is for Master and undergraduate courses of aerospace engineering and physics. It is also aimed at both non-specialists and professionals involved in laboratory testing for space qualification.